Performance of Derived Laboratory Biomarkers with Regard to 30-Day Mortality in Kidney Transplant Recipients with COVID-19 - Domjanović, Josipa; Domjanović Škopinić, Tea; Radić, Josipa; Luketin, Mirko; Jeličić, Ivo; Matetic, Andrija (Life (Basel, Switzerland), 2022)
There are limited data on the performance of laboratory-derived biomarkers in kidney transplant recipients (KTR) with COVID-19. This observational study enrolled 65 KTR with COVID-19 who were treated at the University Hospital of Split up to March 2022. Laboratory-derived biomarkers (neutrophile-to-lymphocyte (NLR) ratio, platelet-to-lymphocyte ratio, monocyte-to-lymphocyte ratio, De Ritis ratio, C-reactive protein (CRP)-to-albumin ratio, lactate dehydrogenase (LDH)-to-hemoglobin ratio, CRP-to-lymphocyte ratio, red cell distribution width-to-albumin ratio, platelet-to-albumin ratio, D-Dimer-to-albumin ratio, D-Dimer-to-NLR ratio, LDH-to-albumin ratio, and LDH-to-white blood cell (WBC) ratio) were calculated, and their performance with regard to 30-day mortality was determined. Mortality events occurred in 12 patients (18.5%), which was significantly associated with increased De Ritis (HR 3.83, 95% CI 1.57–9.35, p = 0.003), CRP-to-albumin (HR 1.36, 95% CI 1.13–1.64, p = 0.001), LDH-to-hemoglobin (HR 1.44, 95% CI 1.07–1.92, p = 0.015), CRP-to-lymphocyte (HR 1.03, 95% CI 1.01–1.07, p = 0.003), D-dimer-to-albumin (HR 4.94, 95% CI 1.38–7.24, p = 0.038), LDH-to-albumin (HR 1.20, 95% CI 1.05–1.36, p = 0.008), and LDH-to-WBC (HR 1.03 95% CI 1.01–1.05, p = 0.024) ratios. Out of these, the best area-under-the-curve (AUC) values were achieved with De Ritis (AUC 0.691), CRP-to-albumin (AUC 0.764), LDH-to-hemoglobin (AUC 0.877), CRP-to-lymphocyte (AUC 0.739), and LDH-to-albumin (AUC 0.827) ratios, while the best discrimination displayed LDH-to-hemoglobin ratio (Harrell’s C 0.808 and Somers’ D 0.616). The overall calibration was satisfactory for all models. Derived laboratory biomarkers such as the de Ritis, CRP-to-albumin, LDH-to-hemoglobin, CRP-to-lymphocyte, and LDH-to-albumin ratios show significant association and discrimination with all-cause mortality in KTR with COVID-19, suggesting its potential risk stratification role.